Thermochemistry of Alkali Metal Cation Interactions With Histidine: Influence of the Side Chain - Armentrout, Peter B.; Citir, Murat; Chen, Yu; Rodgers, Mary T. (My University, 2012)
The interactions of alkali metal cations (M+ = Na+, K+, Rb+, Cs+) with the amino acid histidine (His) are examined in detail. Experimentally, bond energies are determined using threshold collision-induced dissociation of the M+(His) complexes with xenon in a guided ion beam tandem mass spectrometer. Analyses of the energy dependent cross sections provide 0 K bond energies of 2.31 ± 0.11, 1.70 ± 0.08, 1.42 ± 0.06, and 1.22 ± 0.06 eV for complexes of His with Na+, K+, Rb+, and Cs+, respectively. All bond dissociation energy (BDE) determinations include consideration of unimolecular decay rates, internal energy of reactant ions, and multiple ion-neutral collisions. These experimental results are compared to values obtained from quantum chemical calculations conducted previously at the MP2(full)/6-311+G(2d,2p), B3LYP/6-311+G(2d,2p), and B3P86/6-311+G(2d,2p) levels with geometries and zero point energies calculated at the B3LYP/6-311+G(d,p) level where Rb and Cs use the Hay-Wadt effective core potential and basis set augmented with additional polarization functions (HW*). Additional calculations using the def2-TZVPPD basis set with B3LYP geometries were conducted here at all three levels of theory. Either basis set yields similar results for Na+(His) and K+(His), which are in reasonable agreement with the experimental BDEs. For Rb+(His) and Cs +(His), the HW* basis set and ECP underestimate the experimental BDEs, whereas the def2-TZVPPD basis set yields results in good agreement. The effect of the imidazole side chain on the BDEs is examined by comparing the present results with previous thermochemistry for other amino acids. Both polarizability and the local dipole moment of the side chain are influential in the energetics. © 2012 American Chemical Society. © 2013 Elsevier B.V., All rights reserved.; MEDLINE® is the source for the MeSH terms of this document.
Keywords: Histidine; Cations; Histidine; Metals, Alkali; Alkali Metal Cations; Basis Sets; Bond Dissociation Energies; Bond Energies; Collision-Induced Dissociation; Effective Core Potential; Energy Dependent; Internal Energies; Ion-Neutral Collisions; Polarizabilities; Polarization Functions; Quantum Chemical Calculations; Side-Chains; Unimolecular Decay; Zero-Point Energies; Bond Strength (Chemical); Cesium; Complexation; Decay (Organic); Polarization; Quantum Chemistry; Thermochemistry; Xenon; Amino Acids; Alkali Metal; Cation; Histidine; Article; Chemistry; Quantum Theory; Temperature; Cations; Histidine; Metals, Alkali; Quantum Theory; Temperature